The Effect of S.N.I.P.S Strategy on the Achievement of Fifth Grade Students in Geography (Journal Of Educational and Psychological Researches, 2022)
The present research aims at identifying the impact of S.N.I.P.S strategy on the achievement of fifth grade students in natural geographyFor the purpose of verifying the objective of the research, the researcher put the following zero hypothesis: There is no statistically significant difference at the level of (0.05) between the mean score of experimental group who study according to the (S.N.I.P.S) strategy, and the mean score of control group who study according to the traditional method in the achievement test. In order to verify the validity of this null hypothesis, the researcher adopted the experimental method. Two groups of (60) fifth grade literary students were collected randomly from the General Directorate of Education at Baghdad / Karkh III to form the study sample, 30 students for each experimental and control groups.After identifying the scientific material that included the last three chapters of the natural geography book to be taught to the fifth grade students for the academic year (2017 - 2018) in Iraq, the content of that article was analyzed for the purpose of determining their behavioral goals according to Bloom's classification of the field of knowledge and its six levels. The researcher prepared (26) teaching plan for each group as well as he designed an achievement test consisted of (32) items, (26) multiple choices questions and (6) essay questions. There were statistically significant differences at (0.05) between the mean score of the students of the experimental group who studied according to S.N.I.P.S strategy and the mean score of the control group students who studied according to the traditional method.In the light of the results above, the researcher came out with some suggestions and recommendations for future studies.